Students anxiety: an examination of the perception of facial threat and perceived paternal and maternal parenting style - Mustapha Roslinda, Shahadan Md Azman, Abdul Wahab Khan Rahmatullah Khan, Stephan Ian, Archer Marc, (Universiti Pendidikan Sultan Idris, 2017)
Students anxiety: an examination of the perception of facial threat and perceived paternal and maternal parenting style by Mustapha Roslinda, Shahadan Md Azman, Abdul Wahab Khan Rahmatullah Khan, Stephan Ian, Archer Marc,